(untitled) (Scripta : English Department Journal, 2026)
This study investigates the difficulties experienced by upper secondary students at Phanowittayakom School, Thailand, in producing English vowels. Employing a qualitative descriptive design, the research involved 29 students from Grade 5 and Grade 6 who participated in a reading aloud test based on a 158-word narrative text. The students’ oral performances were recorded and analyzed to identify patterns of vowel production errors. The findings reveal persistent difficulties in vowel quality, and vowel length distinction. Common error patterns include vowel substitution influenced by first language interference, simplification of diphthongs, and instability in maintaining long and short vowel contrasts. In addition, questionnaire data indicate that students perceive pronunciation as challenging due to prosodic complexity, cognitive demands, and affective factors such as low confidence. The study highlights that vowel production difficulties are multidimensional, involving linguistic and psychological aspects. These findings suggest the need for explicit phonological instruction, increased phonological awareness, and supportive speaking practice to improve vowel accuracy among EFL learners.